Corporate Social Responsibility in Healthcare: A case of Islamic Banks (IBs) in Bangladesh - Hossain, Md Shamim; Yahya, Sofri B; Rahman, Shafiqur; Sobhani, Farid A; Rahman, Raufa (Bangladesh Journal of Medical Science, 2019)
Healthcare is a basic necessity for any society. Banks in Bangladesh are engaged in Corporate Social Responsibility initiatives better than ever. Islamic banks (IBs)in Bangladesh have taken several CSR initiatives and contributing significantly to healthcare. The main objective of this study is to investigate the CSR practices of Islamic banks (IBs) in the healthcare sector during 2010–2015. The study used a content analysis methodology to analyze objectively and systematically the websites and annual reports of the IBs and the relevant publications of the central bank of Bangladesh. The findings of this study demonstrate that IBs are engaged in healthcare initiatives, which have been increasing significantly over a period of time. However, the results also portrayed that, among all the IBs, Islamic Bank Bangladesh Limited has done the highest contribution in healthcare CSR by establishing hospitals, operating health camps, providing medical assistance, assistance to mother and neonatal etc. This study has also contributed significantly to the relevant literature and paved the path for future research. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.567-573